Hypouricemia and nephroprotection of Coix lacryma-jobi L. seed extract - Ormjai Taejarernwiriyakul; Naohiko Anzai; Promsuk Jutabha; Wantika Kruanamkam; Suparat Chanluang (Songklanakarin Journal of Science and Technology (SJST), 2015)
The Coix lacryma-jobi L. or Adlay seed has been used as a healthy food and herb in many Asian countries. A previous in vitro study found that it has an inhibitory effect on xanthine oxidase (XOD) activity but its use as a traditional medicine in the treatment of hyperuricemia and gout has a lacked scientific evidence. This study aimed to investigate the effects of Adlay seed extract on the level of plasma uric acid (Pua), reduction in fractional excretion of urate (%FEua), decreasing creatinine clearance (Ccr), and increasing plasma creatinine and urea nitrogen in hyperuricemic mice. The steps of the study comprised collecting and inducing the sample mice by giving potassium oxonate and uric acid and treating the hyperuricemic mice by giving Adlay seed extract at doses of 0.1 to 100 mg/kg for 10 days. The results showed that Adlay seed extract significantly reduced Pua in a dose-dependent manner, increased %FEua and Ccr to normal level at doses of 10 and 100 mg/kg and also inhibited XOD activity in liver and plasma in hyperuricemic mice. From this results indicated that Adlay seed extract has hypouricemia and nephroprotective action in hyperuricemic mice.